Dose verification of 3D printed male pelvic phantom for radiotherapy quality assurance - Maniam, Peraveen M (Universiti Sains Malaysia, 2024)
Prostate cancer is a serious health concern worldwide, and its treatment includes advanced radiotherapy techniques that requires patient-specific quality assurance (PSQA) for safety and accuracy of the treatment. Commercially available PSQA phantoms are homogeneous and fail to mimic photon interactions in the pelvis. Therefore, a heterogeneous 3D printed male pelvic phantom was developed to replicate the male pelvis. In this study, the phantom material was characterized by its physical density and computed tomography (CT) numbers and profile. In addition, dose verification was conducted using the phantom with thermoluminescent dosimeter-100 (TLD-100) and ionisation chamber. The results show that the phantom matches the density of real human organs with a maximum difference of 0.22 g/cm3 for prostate. The CT numbers measured at 120 kV well matched with the CT number of real organ with differences ranging from 12.30 HU to 189.77 HU. CT profiles at 90 kV, 120 kV, and 140 kV exhibited consistent gray values with small variation and overlapping standard error bars, indicating high uniformity in the 3D printing. Dose verification using the 3D printed male pelvic phantom revealed in 3D-CRT plans that TPS calculations agreed within ±5% and ±2% for TLD-100 and ionisation chamber measurements, respectively. The Mann-Whitney U test for 3D-CRT showed no significant differences between TPS calculated dose and the dosimeters measured dose (p > 0.05). In VMAT plans, the TPS calculations showed lower doses in the GTV compared to measurements by TLD-100 (deviations: -14.1% to -17.1%) and ionisation chamber (deviation: -4.8%), despite no statistically significant difference found by the Mann-Whitney U test (p > 0.05). In conclusion, the dose calculations and measurements using the 3D printed male pelvic phantom in 3D-CRT plans demonstrated agreement within acceptable limits, but further verification is essential to ensure accurate dosimetry in VMAT plans.